Implementasi Pendekatan Kontekstual terhadap Keterampilan Menggambar dan Membaca Gambar Teknik Siswa Kelas XI Teknik Pengelasan Logam di SMK Negeri 2 Painan - Husna Lathifah Sadli; Nelvi Erizon; Waskito Waskito; Junil Adri (TSAQOFAH, 2026)
Although the ability to read and draw technical drawings is an essential competency in the field of Welding Engineering, Grade XI Welding Engineering (TPL) students at SMK Negeri 2 Painan still experience difficulties in understanding welding symbols, joint forms, and technical dimensional measurements, which results in errors during workshop practice. This study aims to improve students’ technical drawing reading and drawing skills through the implementation of the Contextual Teaching and Learning (CTL) approach. This study used a Classroom Action Research design conducted in two cycles, with each cycle comprising the stages of planning, action implementation, observation, and reflection. Data were collected through multiple-choice tests to measure cognitive ability in reading technical drawings, practical tests to assess drawing skills, and observation sheets to record learning activities. The results showed that the implementation of CTL through inquiry activities, modeling using real workpieces, group discussions, and the formation of a learning community was able to consistently improve students’ learning outcomes from the pre-cycle stage to Cycle I and Cycle II. This improvement was reflected in students’ ability to identify welding symbols, read technical measurements, and produce drawings according to standards. The conclusion of this study affirms that the CTL approach is effective in improving learning mastery, reducing gaps in understanding, and strengthening students’ vocational competency readiness in accordance with industry needs. These findings provide practical implications for vocational teachers in developing technical drawing instruction that is more contextual, applicable, and relevant to workshop work practices.